Global Sources strategic drives in global trade - Pangan, Connie (Animo Repository, 2006)
Global Sources is a leading business-to-business (B2B) media company that facilitates global trade, with a particular focus on the China market, by providing information to international buyers and integrated marketing services to suppliers. The company helps buyers source more effectively by enabling them to identify and evaluate products and suppliers. It helps suppliers introduce new products, develop new markets, enhance their image, and generate valuable sales contacts that lead to profitable orders through its total solution package online, print and trade shows. For buyers and suppliers, each media format plays a different, yet complementary role in the buying process. For example, print advertising contributes greatly to making buyers aware that a company is a potential supplier. It allows a company to powerfully differentiate itself from its competitors and often stimulates the buyer to make an inquiry or visit its website. The website enables the supplier to present buyers with far more information on their products and manufacturing capabilities than it could with a magazine advertisement. Trade shows, on the other hand, facilitate face-to-face meetings and ordering activities that cannot be accomplished by print or online media An integrated marketing campaign using online, print and tradeshow media also gives suppliers the opportunity to reach a much greater percentage of their potential customers than they would reach using one, or even two types of media. Integrated campaigns that surround a supplier's prospective customers from various touch points will increase buyers awareness and interest, enhance the company's brand or image, and increase the likelihood of the buyer making an inquiry. Despite the excellent performance of the integrated media, Global Sources existing e-market model will not survive in the future. The company will not be able to sustain long-term growth if it does not consider looking into improving its online service from matchmaking to integrated product system. Why? New trends are characterizing the e-commerce environment: The market is consolidating and good business concepts no longer suffice for sustainable success. Instead, wise sayings of the old economy like cost-efficiency, turnover, and profit maximization using known assets like business process management, innovation, and collaborations are being focused. e-commerce requires a good management of business processes since crucial processes are in direct interaction with customers. Collaboration based on aligned business processes enables integrated products and services with a single interface to customers. The competition is rising along with the market consolidation and causes shrinking margins. For the profit and turnover maximization, it is therefore necessary to raise the amount of transactions and to achieve business process efficiency.